Eskimo women with infants, Cape Prince of Wales, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Eskimo women showing their manner of carrying their Young. Cape Prince of Wales, Alaska. Nowell To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number